Dosage-dependent reduction of macular pigment optical density in female breast cancer patients receiving tamoxifen adjuvant therapy - Lim, I-Liang; Loo, Angela Voon Pei; Subrayan, Visvaraja; Khang, Tsung Fei; See, Mee Hoong; Alip, Adlinda; Taib, Nur Aishah Mohd (Elsevier, 2018)
It is now increasingly common for breast cancer patients to receive adjuvant tamoxifen therapy for a period of up to 10 years. As survival rate increases, managing tamoxifen ocular toxicities is important for patients' quality of life. Macular pigments in photoreceptor cells protect against free radical damage, which can cause macular degeneration. By reducing macular pigment concentration, tamoxifen may increase the risk of macular degeneration. Here, we compared macular pigment optical density (MPOD) and central macular thickness between breast cancer patients on tamoxifen adjuvant therapy (n = 70), and a control group (n = 72). Multiple regression analysis indicated that MPOD decreases with increasing tamoxifen dosage, up to a threshold of about 20 g, after which MPOD plateaus out. Mean MPOD in the treatment group (mean = 0.40) was significantly lower (p-value = 0.02) compared to the control group (mean = 0.47) for the left eye, and for the right eye (treatment mean = 0.39; control mean = 0.48; p-value = 0.009). No significant difference in mean central macular thickness was found between the treatment and the control group (p-values > 0.4). In the control group, MPOD and central macular thickness showed significant correlation (r∼0.30; p-values < 0.01) for both eyes. However, in the treatment group, loss of significant correlation was observed in the left eye (r = 0.21; p-value = 0.08). The present results show that MPOD decreases non-linearly as a function of tamoxifen dosage, and highlight the potential of tamoxifen to reduce macular pigment concentration through an unknown mechanism that does not depend on macular thinning solely.